Case Studies in Canadian Health Policy and Management - CATHERINE L. MAH (University of Toronto Press, 2014)
Covering a wide range of issues, Case Studies in Canadian Health Policy and Management is an exceptional resource for bringing real-life policy questions into the classroom. The twenty-two case studies have been developed with input from mid-career professionals with strong field experience, and have been extensively tested in Raisa B. Deber’s graduate case study seminar at the University of Toronto. Each case features both a substantive health policy issue and a selection of key concepts and methods appropriate to examining public policy, public health, and health care management issues. The contributors provide a summary of each case and the related policy issues, a description of events, questions for discussion, supporting information and references, and suggestions for further reading. Suitable for graduate and undergraduate classrooms in programs in a variety of fields, Case Studies in Canadian Health Policy and Management is an exceptional educational resource. This second edition features all new cases, as well as a new introductory chapter that provides a framework and tools for health policy analysis in Canada.